2016
DOI: 10.1590/2179-8087.130715
|View full text |Cite
|
Sign up to set email alerts
|

Equações Hipsométricas, Volumétricas e de Crescimento para Khaya ivorensis Plantada em Pirapora

Abstract: RESUMOO presente trabalho teve como objetivos a disponibilização de equações hipsométricas, volumétricas e de predição do crescimento para a espécie Khaya ivorensis. Para o ajuste das equações de altura utilizaram-se dados de altura total e diâmetro a 1,3 metros de altura coletados em plantio localizado no município de Pirapora, Minas Gerais. Para as equações volumétricas, realizou-se a cubagem de 21 árvores em pé no mesmo plantio. As equações de crescimento foram estimadas com dados de volume por hectare de 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 7 publications
2
10
0
2
Order By: Relevance
“…While some studies have reported growth parameters and wood quality for Khaya ivorensis plantations considering limited stand variations (e.g. Silva et al 2016, Ribeiro et al 2016, to our knowledge, this study is the first to provide height-diameter models for a large scale database in Brazil and beyond. Care must be taken when applying the models outside the sampled database range (for other parts of the world or for ages over 14 years), especially considering the peculiarities of Brazilian African mahogany silviculture (intensive management practices and wide spacing).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While some studies have reported growth parameters and wood quality for Khaya ivorensis plantations considering limited stand variations (e.g. Silva et al 2016, Ribeiro et al 2016, to our knowledge, this study is the first to provide height-diameter models for a large scale database in Brazil and beyond. Care must be taken when applying the models outside the sampled database range (for other parts of the world or for ages over 14 years), especially considering the peculiarities of Brazilian African mahogany silviculture (intensive management practices and wide spacing).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to illustrate the need for calibration of the height-diameter relationship and to adhere to the range of the sampled database, we also plotted a model from Silva et al (2016) in figure 6. These authors presented a local equation fitted with NLS method to predict height in 4-year-old African mahogany stands geographically close to some of the stands used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diante disso, surgiu a necessidade de se obter espécies florestais com características anatômicas semelhantes, com mesmas utilizações e passíveis de corte. Como alternativa, por ser uma espécie semelhante ao mogno nativo e resistente a sua principal praga, à broca-do-ponteiro (Hypsipyla grandella (Zeller)), além de proporcionar um crescimento relativamente acelerado, o mogno africano (Khaya ivorensis A. Chev), pertencente à família Meliaceae, foi introduzido no Brasil com a finalidade de suprir a demanda pelo mogno brasileiro (SILVA et al, 2016;RIBEIRO et al, 2017).…”
Section: Introductionunclassified